How Russia uses science to justify the annexation of Ukrainian territories - Alex Plastun; Tetiana Hryn'ova; Vіacheslav Plastun; Liudmyla Sliusareva; Oksana Kazak (Knowledge & Performance Management)
Type of the article: Research Article This paper explores how Russia uses the international academic sphere, including scientific papers, scientometric databases, international publishers, and international organizations, as a propaganda tool to legitimize its appropriation of Ukrainian territories and Ukrainian academic institutions there. To do this, a bibliometric analysis was used. The results showed that thousands of academic papers published in 2014–2024 in peer-reviewed journals by Russian academicians marked Ukrainian territories as those referring and affiliated with the Russian Federation. The same is true for the case of editorial boards of international journals, where Ukrainian cities were incorrectly marked as part of the Russian Federation. Quite often, those organizations that provide affiliations in the occupied territories of Ukraine are not even legitimate: they were created by Russia using the captured Ukrainian scientific infrastructure and often named similarly or the same as the existing Ukrainian institutions-in-exile. It is important that the international scientific community put an end to this misuse of its resources. The study findings highlighted the importance and urgency of coordinated actions from academic journals, publishing platforms, and scientometric databases towards vigilant oversight of the content they host and accountability of the authors to prevent the dissemination, indexing, or promotion of Russian narratives and propaganda related to the appropriation of the Ukrainian territories. Acknowledgment Alex Plastun gratefully acknowledges financial support provided by Volkswagen Foundation, Ref.: 9C853, Project “Sustaining Ukrainian Scholarship”, hosted by New Europe College.